A study on advertising practices of Islamic banks in Malaysia: an empirical assessment under Islamic observation - Haque, A. K. M. Ahasanul; Sayyed Ahmad, Mohd. Ismail; Rahman, Sabbir (2010)
Investigation of advertising of Islamic bank and its evaluation under Islamic observation is a significant issue for most marketers given the conventional and Islamic Banks are all facilitating numerous marketing activities across the nations. Therefore, it is reckoned as a theme of research within intellectual milieu. The current research looked into determinants of advertising practices by the Islamic bank in Malaysia. Results indicated that there have strong relationships among encouragement of good deeds, morality, truthfulness towards evaluation and effectiveness of advertisement of the Islamic banks. Hence, this paper strongly attempts to examine their relationship as well. In addition most of the respondents confirmed that most of the Islamic bank practices decent advertisement though some of the respondents suggest that advertisements by the Islamic bank need more supervision. Findings from this research should be used having in consideration the limitation in which the study was conducted. Given the financial and time constraints, the current research was limited. The study was conducted only in few Islamic Banks with limited number of employees. Further research should be considered to gather more information regarding the service quality and customers’ satisfaction dimensions in context of the Malaysian Islamic and conventional bank. It is hoped that the findings of this study will assist the Islamic banks in what they can produce their services and how they want to promote their services as well?